Evaluasi Program Tahfizh Weekend di SMP IT Wahdah Islamiyah Gowa dengan Model CIPP - Hasta, Muharrida; Syamsudduha, St. (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Education is an important aspect of life that plays a major role in producing a quality generation. One important part of Islamic education is teaching the Qur'an from an early age. The Tahfizh Weekend Program at SMP IT Wahdah Islamiyah Gowa is an effort to improve students' memorization of the Qur'an through an intensive approach involving memorization learning, daily worship, and social activities. This study aims to evaluate the effectiveness of the program using the CIPP (Context, Input, Process, Product) evaluation model, focusing on context analysis, input components, process implementation, and the results obtained. The research method used is a descriptive approach with in-depth interviews and participatory observation. The results of the study showed that this program succeeded in improving students' memorization of the Qur'an, with 78% of students experiencing an increase in the number of memorizations. This program also has a positive impact on the formation of students' religious character, increasing discipline in worship, and strengthening social relationships between students. However, several obstacles such as limited facilities and environmental disturbances need to be considered. Parental support is also an important factor in the success of this program. This study suggests improvements in terms of facilities and time management to increase the effectiveness of the program in the future. The output of this study is expected to provide strategic recommendations for the development of similar programs in other schools.